Survei Sarana dan Prasarana Pendidikan Jasmani Olahraga dan Kesehatan di SDN Se-Kecamatan Purwosari Kabupaten Pasuruan - Hakim, Randi Ahmad Fikril; Amiq, Fahrial (Populer: Jurnal Penelitian Mahasiswa, 2025)
The learning process of physical education is similar to the learning process of other lessons, where there is interaction in the learning and also a change in attitude for the better. Facilities are all facilities needed for the teaching and learning process, both indoors and outdoors, so that the objectives of this learning research are achieved properly, organized, efficient, and effective. Educational infrastructure is a number of facilities that indirectly facilitate, such as school yards, gardens, and roads leading to school. This research aims to find out and examine how PJOK facilities and infrastructure in State Elementary Schools in Purwosari District, Pasuruan Regency. The data collected through interviews and observations were then analyzed through descriptive quantitative data processing using Microsoft Excel. The determination of the sample was carried out using the Slovin formula with a predetermined error rate of 20%, so the total sample was obtained from 14 State Elementary Schools. The results of the study showed that the existence, condition and ownership status of physical education, sports and health facilities in State Elementary Schools in Purwosari District were in category E with an average overall percentage of 42%. For infrastructure in category E with a percentage of 28.5% feasible, This shows that there are still many facilities that do not meet the requirements and completeness. Based on these results, the researcher suggested that there is a need for accuracy in the distribution of funds for facilities and infrastructure so that the existing facilities and infrastructure meet the standards reviewed from Permendiknas No. 24 of 2007. For teachers, it is also necessary to modify facilities and infrastructure so that existing facilities and infrastructure can still support learning properly.